Nasikh Dan Mansukh Alquran Menurut dr. Hamka - Ruslan Ruslan (JOURNAL OF ISLAMIC AND LAW STUDIES, 2019)
AbstractIs there in the Qur'an nasakh (removed the law of sharak). Ulama differ on this matter. Differences of opinion about two things: first for scholars who say there are scriptures because there are several verses that can be made basic and both facts there are several verses of the Qur'an that are difficult to change must accept the concept of nasakh. For the modern, there is no contradiction in the Koran. There is no proposition that can be used as the basis of the text and if there is a verse that seems difficult to understand, then it must be studied because of its descent, takhshis, sociolinguistics, guidance, and rationality so that our hearts will be peaceful.Keywords: naskh, nasikh and mansukh AbstrakApakah dalam Alquran ada nasakh (penghapusan hukum syarak). Ulama berbeda pendapat dalam hal ini. Perbedaan pendapat tsb disebabkan dua hal: pertama bagi ulama yang menyatakan ada nasakh karena ada beberapa ayat yang dapat dijadikan dasar  dan kedua faktanya ada beberapa ayat Alquran yang sulit dipahami kecuali harus menerima konsep nasakh. Bagi ulama  yang modern menyatakan Alquran tidak ada yang kontradiksi . Tidak ada dalil yang bisa dijadikan dasar adanya nasakh  dan kalau ada ayat yang kelihatannya sukar dipaham, maka harus dikaji sebab turunnya, takhshis, sosiolinguistiknya, petunjuknya, dan rasionalitasnya maka hati kita akan damai. Kata-kata kunci: naskh, nasikh dan mansukh